Efektivitas Pencabutan Pembebasan Bersyarat Terhadap Warga Binaan Pemasyarakatan Klien Balai Pemasyarakatan Kelas II Gorontalo - Taroreh, Marten Verdinan; Darmawati, Darmawati; Beddu, Sumiyati (Jurnal Litigasi Amsir, 2025)
Implementation of parole revocation for prisoners at the Correctional Center Class II Gorontalo. This study aims to understand the legal basis, procedures, and impact of parole revocation on prisoners, as well as evaluate the consistency of the application with applicable correctional principles. The method used is juridical-empirical, by collecting data through interviews with correctional officers, and correctional center clients, and analysis of related documents. The results show that there are cases where there is a non-optimal revocation of parole, which has the potential to cause injustice and hamper the process of rehabilitation and reintegration of prisoners into society. Recommendations include the need for increased training and supervision for correctional officers, strengthening the complaint mechanism and appeal process for prisoners, and policy adjustments to ensure a fairer and more effective application of parole rights.